Design and Implementation of Secure Stream Cipher Algorithm - Sagheer, Ali M; Salih, Salih S; Searan, Sura M (International Journal of Computing and Digital System (Jāmiʻat al-Baḥrayn. Markaz al-Nashr al-ʻIlmī), 2018)
RC4 stream cipher is an encryption algorithm that is used in two domains of security realized for IEEE 802.11 LANs: one of them is wired equivalent confidentiality and the other is WI-FI Protected Access protocol. It is symmetric encryption, fast, and simple algorithm. It has different weaknesses such as the bias that occurs in the key stream bytes. Key scheduling phase is more intricate. It was prepared to be unnecessarily easy. The initial few bytes of keystream that are generated by pseudo random generation algorithm (PRGA) are biased to several bytes of the private key. Thus, the byte analysis makes it probable for attacking RC4 in some methods of operations. This paper presents a new stream cipher algorithm as a development for RC4, named double RC4 key generation, which is submitted to solve interconnection problems in the output of the inner state and solve the problem of weak keys. The new idea allows random access to the key stream. The keystream depends on all preceding state bytes. RC4 and the proposed algorithm are analyzed and proved that the new algorithm has no single or double byte bias in the key stream while RC4 has proved the same bias that is shown in the literature. The proposed algorithm introduces high resistance against different attacks that are applied to RC4 and the generated key stream has high randomness, large complexity, and good statistical properties. Keywords: : RC4, Key Scheduling Algorithm (KSA), Pseudo Random Generation Algorithm (PRGA), double RC4 key generation, single bias, double bias.